ANALISIS KUALITAS PELAYANAN PENGGUNAAN SISTEM PASPOR TERPADU BERBASIS BIOMETRIK (SPTBB) TERHADAP KEPUASAN USER (STUDI KASUS DI DINAS IMIGRASI KOTA SEMARANG) - Tita Talitha; Adi Prasetya (TECHNO SCIENCE, 2011)
The aim of this research is to know, is there the influence to use information system of SPTBB for user satisfaction at Imigration Service Office of Semarang. To survey the influence of satisfaction in using information system of SPTBB, on this research consists of independent variable that is tangible, reliability, responsiveness, assurance, emphaty and dependent variable that is SPTBB user satisfaction. This research is using analysis of classic assumption test, double regretion test, F test, and t test. Base on the research result that all of servive quality variable concurrently is tangible, reliability, responsiveness, assurance, dan emphaty take effect for user satisfaction with sig value 0.000 < 0.05 and partially from all of service quality variable, takes effect for user satisfaction of SPTBB. Dimension of responsiveness has biggest effect for user satisfaction of SPTBB information system with sig value 0.045 < 0.05. As for the other dimension is tangible with sig value 0.000, reliability 0.006, assurance 0.027, and emphaty 0.020.